THE EFFECT OF GAMBIER EXTRACT ON THE LEVELS OF MALONDIALDEHYDE, SUPEROXIDE DISMUTASE, AND BLOOD GLUCOSE IN TYPE 2 DIABETES MELLITUS PATIENTS - Sari Pane, Yunita; Ganie, Ratna Akbari; Lindarto, Dharma; Lelo, Aznan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Diabetes mellitus is a disease associated with dysfunction of pancreatic Î²-cells and oxidative stress. A treatment which can reduce the impact of oxidative stress may be beneficial in the treatment of diabetes. Therefore, this study aimed to investigate the effect of gambier extract on the levels of malondialdehyde (MDA), superoxide dismutase (SOD), and blood glucose level (BGL) in type 2 diabetes mellitus (T2DM). Methods: This research was a randomized clinical study consisted of two groups, namely placebo group (n=10) and gambier group (n=6). The blood samples were collected from the vein after fasting overnight and before consuming 100 g white bread to measure the levels of MDA, SOD, and BGL. The same procedure was conducted after fasting and 2-h postprandial on day 1 and day 14. The data obtained were analyzed with Student’s t-test with a statistical significance level of p<0.05. Results: The results showed that there was no change in MDA levels in the placebo group during the observation, but there was a significant decrease in MDA levels in the gambier group on day 14. In contrast, SOD levels increased in all measurements although there was no change on day 1 in the placebo group. The present study also found a significant increase of BGLs after consuming 100 g bread in both groups, but less BGL elevation in the gambier group. Conclusion: It is concluded that gambier extract has special mechanisms in the treatment of T2DM as an antioxidant and BGLs reduction.